-3+1+6x-4=x+8+5x

Simple and best practice solution for -3+1+6x-4=x+8+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+1+6x-4=x+8+5x equation:


Simplifying
-3 + 1 + 6x + -4 = x + 8 + 5x

Reorder the terms:
-3 + 1 + -4 + 6x = x + 8 + 5x

Combine like terms: -3 + 1 = -2
-2 + -4 + 6x = x + 8 + 5x

Combine like terms: -2 + -4 = -6
-6 + 6x = x + 8 + 5x

Reorder the terms:
-6 + 6x = 8 + x + 5x

Combine like terms: x + 5x = 6x
-6 + 6x = 8 + 6x

Add '-6x' to each side of the equation.
-6 + 6x + -6x = 8 + 6x + -6x

Combine like terms: 6x + -6x = 0
-6 + 0 = 8 + 6x + -6x
-6 = 8 + 6x + -6x

Combine like terms: 6x + -6x = 0
-6 = 8 + 0
-6 = 8

Solving
-6 = 8

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| Z^2(a+b)+z^3(a+b)=0 | | r+7=r+7 | | x/8=50 | | 3x-8=x/2 | | 2000=150m+350 | | -(n-8)+2n=-2 | | 38=5+80+-16t^2 | | 8*3x+5=112 | | 0=-4.9t^2+45t+2 | | 6z^2-15z=0 | | 2(x+10)=10 | | 1+2+3+4-6*6= | | 13x-8+x=-22 | | 8b^2+16b+4=8 | | 4*2=14-N | | 10xX=45 | | 3x+0=28 | | n-(-3.4)=8.3 | | 6(11t-4)-7(6t-1)=47 | | 94=9x+4 | | Y=2/3-6-1= | | X+29+29+x+140=180 | | x/37=18 | | 2x^4+2x^5+2x^10=0 | | -8m+8=-10m-16 | | X+8+x=24 | | -7[8+5x]=-226 | | y=x^(1/6) | | 0.4n=12 | | x/100=50/60 | | 4x-2-x=28 | | [8+(38-14)-10]= |

Equations solver categories